Prevalência do uso de suplementos nutricionais entre praticantes de atividade física em academias de Belo Horizonte: Fatores associados - Janaina Lavalli Goston (2008)
Exercise has become more popular amongst the general population in the last decades. Simultaneously, the intake of nutritional supplements has widely increased, with people using these products for both aesthetic reasons and for better physical performance. Athletes have been the main consumers of nutritional supplements, however little is knownabout their use amongst general members of the population who frequently exercise in gyms. Therefore, it was the objective of the present study to assess the prevalence of use of dietary supplements amongst exercisers from different gyms in the city of Belo Horizonte. Factors associated with the intake of supplements were also evaluated. Thus,1,102 subjects of both genders and all social classes from 50 gyms throughout the city were assessed. It was found that 36.8% (n=405) of people used supplements. The highest intake was amongst men (63.5%). Five products were mostly consumed and they were those rich in proteins and amino acids (58%), isotonic drinks (32%), rich in carbohydrates (23%), natural/phytotherapy (20%) and multivitamins/mineral supplements (19%). The use of two or more simultaneous products occurred in 43.5% of cases. Many participants(55%) reported consuming nutritional supplements without any specialized professional guidance, usually based on self-prescription or recommendation of friend(s), salesmen at the nutrition supplement store and through advertisements. Interestingly, 74% of the gyms had a working dietitian on staff. Some people (14.1%) used supplements as advised by physical trainers, who are not qualified to make such recommendations. Anaerobic activities were performed by the majority of users (87.1%), which together with other variables such as age, concern about aesthetics and body image exerted influence on the decision to consume supplements. On the other hand, educational status did not exert any influence on such decisions. Our results suggest that it is easier to take supplements in detriment of adequate balanced nutrition. The supplements are widely available and are often prescribed by those unqualified to do so. Therefore, increased efforts should be undertaken to educate the general population on the subject, mainly in gyms or sportsareas.